Model pengajaran adab untuk generasi Z dan alpha - Sari, Lidia Trisna; Aryesi, Irma; Eli, Elvi; Dajascan, Yosep; Leni, Fitra (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2026)
Generation Z and Generation Alpha are cohorts that grow and develop in a digital environment, characterized by intensive use of technology, rapid access to information, and interaction patterns that largely take place in online spaces. These characteristics present particular challenges for the teaching of adab (moral conduct) in Islamic educational institutions, as normative values of adab have not been fully internalized into students’ daily behavior, especially in digital contexts. This study aims to formulate and analyze a model of adab teaching that is relevant to the characteristics of Generation Z and Generation Alpha within the framework of Islamic education. The research employs a qualitative approach with a descriptive-analytical design through library research on scholarly literature and educational policy documents, complemented by limited observation of adab teaching practices in several Islamic educational institutions. Data were analyzed using content analysis and critical synthesis techniques. The findings indicate that the main problem in adab education lies in the weak process of internalization and habituation of values due to the dominance of cognitive-oriented approaches and the lack of integration of adab into digital spaces. Based on these findings, the study proposes the A.D.A.B. Teaching Model (Adaptive, Digital, Activative, and Habit-Based) as a contextual and sustainable pedagogical approach that responds to the challenges of the digital generation. Abstrak Generasi Z dan Generasi Alpha merupakan kelompok generasi yang tumbuh dan berkembang dalam lingkungan digital, ditandai dengan intensitas tinggi penggunaan teknologi, akses informasi yang cepat, serta pola interaksi yang banyak berlangsung di ruang daring. Karakteristik tersebut menghadirkan tantangan tersendiri dalam pengajaran adab di lembaga pendidikan Islam, karena nilai adab yang diajarkan secara normatif belum sepenuhnya terinternalisasi dalam perilaku keseharian peserta didik, khususnya dalam konteks digital. Penelitian ini bertujuan merumuskan dan menganalisis model pengajaran adab yang relevan dengan karakter Generasi Z dan Generasi Alpha dalam konteks pendidikan Islam. Penelitian menggunakan pendekatan kualitatif dengan desain deskriptif-analitis melalui studi kepustakaan terhadap literatur ilmiah dan dokumen kebijakan pendidikan, yang dipadukan dengan observasi terbatas pada praktik pembelajaran adab di beberapa satuan pendidikan Islam. Analisis data dilakukan menggunakan teknik analisis isi dan sintesis kritis. Hasil penelitian menunjukkan bahwa permasalahan utama pendidikan adab terletak pada lemahnya proses internalisasi dan pembiasaan nilai akibat dominasi pendekatan kognitif serta belum terintegrasinya adab dalam ruang digital. Berdasarkan temuan tersebut, dirumuskan Model Pengajaran Adab A.D.A.B. (Adaptif, Digital, Aktivatif, dan Berbasis Kebiasaan) sebagai pendekatan pedagogis yang kontekstual, berkelanjutan, dan relevan dengan tantangan generasi digital.